MATERIAL FLOW RELATIONS IN THE DESIGN PROCESS OF MATERIALS HANDLING - Telek, Péter (Advanced Logistic Systems - Theory and Practice, 2016)
Handling relations are often used in every field of logistics, mainly at the design of materials handling processes and systems. Despite this, definitions and determinations of the handling relations are not published in suitable details in the literature. The aim of my research to analyse the handling relations, define the materials handling matrices and their application possibilities in the design process. In this paper I describe the handling relations and the possible devices to take them into account. Beside it, I summarise main types, definitions, characterisations and structures of materials handling matrices, and show their determination methods through a simple example.